2003
DOI: 10.1046/j.1365-2761.2003.00483.x
|View full text |Cite
|
Sign up to set email alerts
|

White spot syndrome virus infection in cultured Penaeus vannamei (Boone) in Ecuador with emphasis on histopathology and ultrastructure

Abstract: Mortalities of cultured shrimp, Penaeus vannamei (Boone), induced by white spot syndrome virus (WSSV) have occurred in Ecuador since May 1999. Three epidemiological surveys in Ecuadorian farms were carried out and showed an apparent association between lower temperature and increased mortality rates in commercial ponds. Infected animals showed a reddish discolouration and lethargy and occasionally, white spots in the exoskeleton. Histopathological studies revealed that infected cells presented nuclear hypertro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
0
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(58 citation statements)
references
References 27 publications
4
50
0
4
Order By: Relevance
“…Os valores das análises físico-químicas da água e solo, tempo de coagulação da hemolinfa e presuntivo de víbrios, quando observada a distribuição normal e a homogeneidade das variâncias, foram analisados por meio do teste de comparação de médias "Z" e, caso contrário, pelo teste não paramétrico de Mann Whitney, tendo-se considerado o nível mínimo de significância de 5%. (Rodríguez et al, 2003). Pérez et al (2005) sugerem que as pós-larvas podem ser a fonte inicial da carga viral, considerando-se também a possibilidade de aumento da doença ou mesmo de a fonte do vírus ocorrer em consequência de portadores positivos, que fazem parte do habitat ou da dieta normal dos camarões.…”
Section: Methodsunclassified
“…Os valores das análises físico-químicas da água e solo, tempo de coagulação da hemolinfa e presuntivo de víbrios, quando observada a distribuição normal e a homogeneidade das variâncias, foram analisados por meio do teste de comparação de médias "Z" e, caso contrário, pelo teste não paramétrico de Mann Whitney, tendo-se considerado o nível mínimo de significância de 5%. (Rodríguez et al, 2003). Pérez et al (2005) sugerem que as pós-larvas podem ser a fonte inicial da carga viral, considerando-se também a possibilidade de aumento da doença ou mesmo de a fonte do vírus ocorrer em consequência de portadores positivos, que fazem parte do habitat ou da dieta normal dos camarões.…”
Section: Methodsunclassified
“…Research conducted by Rodríguez et al (2003) suggested an apparent association between lower temperature and increased shrimp mortality rates. Thus, given importance of this industry and the limitations of high-intensity cultivation due to viral infections causing high mortality (Ramos-Carreño et al, 2014;Melena et al, 2015), particularly in extreme salinities (50), the development of prevention methods against WSV and other viruses would be necessary (Witteveldt et al, 2004a(Witteveldt et al, , 2004b).…”
Section: ______________________mentioning
confidence: 99%
“…In 2014, P. vannamei culture generated an annual revenue of 150 million dollars in Ecuador (FAO, 2012). Moreover, the shrimp culture industry has been affected by several viral and bacterial diseases (Lightner, 2011), most importantly white spot syndrome virus (WSSV) due to its high mortality rate (Rodríguez et al, 2003).…”
mentioning
confidence: 99%
“…Hal ini bukan karena penyakit virus sebagai penyebab utamanya yang dapat diatasi, akan tetapi terutama karena subtitusi dari udang windu ke vaname, meskipun pada kenyataannya bahwa udang vaname juga tidak terlepas dari serangan penyakit terutama WSSV (Rodriguez et al, 2003;SanchezMartinez et al, 2007). Penggunaan bakteri probiotik sebagai bakteri pengurai bahan organik juga memberikan kontribusi terhadap perbaikan lingkungan budidaya yang berefek pada peningkatan kesehatan udang sehingga tidak mudah stres dan terserang penyakit.…”
Section: Pendahuluanunclassified